Bah - Salsabila Ghina Luthfiyah; Intan Nevia Cahyana (Reformasi Hukum Trisakti, 2023)
Infrastructure development in Indonesia, such as the construction of Ring Road II by the Manado City Government, aims to enhance welfare. However, the land acquisition process for this project does not align with the procedures outlined in Law Number 2 of 2012 regarding Land Procurement for Public Interest Construction. The research investigates the land acquisition process and assesses whether Decision Number 661/Pdt.G/2021PN Mnd complies with the law. Using descriptive normative research with secondary data, the study reveals that the Manado City Government's land acquisition process lacks conformity with the legal preparatory stages specified in Articles 18 and 19 of Law Number 2 of 2012. Consequently, the considerations and decision in Judge's Decision Number 661/Pdt.G/2021PN Mnd align with the law.